Accountability Gaps in the Single Supervisory Mechanism (SSM) Framework - Karagianni, Argyro; Scholten, Miroslava (Utrecht Journal of International and European Law, 2018)
The first judgement of the General Court (EU) pertaining to the Single Supervision Mechanism (SSM) raised an issue concerning the source of the shared supervisory powers in the system of EU prudential supervision. In the General Court’s view, the SSM Regulation conferred on the European Central Bank (ECB) exclusive powers to carry out specific prudential supervisory tasks vis-à-vis all euro area credit institutions (significant and less significant). At the same time, the ECB’s national counterparts assist the former in implementing its supervisory tasks vis-à-vis less significant credit institutions. We argue that such a scheme requires a clear accountability relationship also between the ECB and the national competent authorities (NCAs), something that is not fully fledged in the current legal framework.